IDENTIFIKASI KENYAMANAN TERMAL RUANG PADA RUMAH BETANG ENSAID PANJANG DI KABUPATEN SINTANG - Meidycharlos Amos Ondion Situmeang; Tri Wibowo Caesariadi; Uray Fery Andi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Traditional architecture is an architectural form that passed down from one generation to the next. Traditional houses are formed through a long time that are responsive to the environment. The traditional houses adapt with the environment to increase their level of comfort and reduce disturbances for a comfortable living. This study aimed to identify the thermal comfort of Betang Ensaid Panjang, which is the traditional Dayak houses in Sintang Regency. Identification of the thermal comfort was done by measuring the influential thermal variables; air temperature, humidity, wind speed, the clothing insulation and the metabolism at Betang Ensaid Panjang. As a building that located in a tropical climate, an analysis of the tropical architecture theories was carried out at Betang Ensaid Panjang. The results of the analysis become the hypothesis that the building applies the principles of humid tropical architecture. Based on PMV and PPD analysis by ASHRAE 55 Standard, it can be identified that the Betang Ensaid Panjang have different levels of thermal comfort in ruai, bilik and tingkak at different times. In the morning it can be identified as slightly cool, in the afternoon and evening, can be identified as slighltly warm and at night, it can be identified as neutral or comfort.